Impingement cooling by round jet with longitudinal swirling strip - Kunnarak, Kengkla; Somravysin, Prachya; Eiamsa-Ard, Smith; Chuwattanakul, Varesa (My University, 2018)
The objective of this research is to study the effect of swirling impinging jet on the heat transfer in the impinged plated by using thermochromic liquid crystal (TLC) sheet. In the experiments, the nozzle having a diameter of 20 mm (D) was installed with four-channel twisted tape as a longitudinal swirling strip. The jet impingement was performed at jet-to-plate distances (L/D) of 2, 3, 4, 5, 6 and 7, and constant Reynolds number (Re) of 5000. The experimental results showed that the swirling jet induced by the four-channel twisted tape gave higher heat transfer rates than the conventional jet at the same operating conditions. The highest average heat transfer rate was obtained at the jet-to-plate distance (L/D) of 2.
Keywords: Heat transfer; Swirl generator; Swirling impinging jet; Thermochromic liquid crystal